The Information-Related Time Loss on Construction Sites: A Case Study on Two Sites. (22nd August 2014) - Xu, Sheng; Luo, Hanbin
Information management is essential in construction projects. Existing research has identified and discussed problems in communication and information transfer among different stakeholders, such as the loss of information caused by fragmentation and information islands. However, there are few statistics about the direct time waste caused by information loss arising from poor communication and information management. Existing surveys relying on self-reporting questionnaires and interviews often contain various biases. This paper presents a direct observation of two construction sites in China in relation to wasted time and the information flows in these time-wasting events. Analysis of the observation data provides objective and comprehensive statistics on time wasted due to inconsistent information, dislocation and ambiguity. This research also analyses the correlation between participants, information carriers, information loss and the amount of time wasted. Finally, the wasting of time is analysed from the perspective of information flows and problems that cannot be addressed by information technologies are discussed.